Tadrīj Method in Hajj Fund Management by Badan Pengelola Keuangan Haji (BPKH) in Indonesia: A Study of Islamic Economic Law - Muslim, Moch. Bukhori; Khan, M. Dawud Arif; Saepullah, Saepullah; Hendarsa, Agung Sri; Afif, Ahmad (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2026)
Background: The governance of Hajj funds in Indonesia, administered by the Badan Pengelola Keuangan Haji (BPKH), represents a complex intersection between Islamic legal norms and modern financial management. Although formally regulated under Law No. 34/2014 and reinforced by Majelis Ulama Indonesia (MUI) Fatwa No. 09/Ijtima' Ulama/VIII/2024, practical challenges remain in ensuring that investment decisions and governance mechanisms consistently reflect Sharia principles. This tension highlights the need for an adaptive approach that reconciles normative compliance with institutional and market realities. Objective: This study aims to examine how the Tadrīj approach can be operationalized in Hajj fund management as a strategic framework to strengthen Sharia compliance while maintaining financial performance and institutional stability. Method: The research employs a qualitative descriptive design, using institutional data from BPKH financial management reports and relevant regulatory documents. Data are analyzed through a normative-empirical approach, integrating legal interpretation with contextual evaluation of governance practices. Findings: The study finds that the application of Tadrīj enables a phased and adaptive integration of Maqāṣid al-Sharīʿah into Hajj fund governance. This gradual approach reduces potential conflicts between strict legal compliance and investment efficiency, while reinforcing transparency and accountability as core institutional pillars. In addition, continuous engagement with Sharia scholars and periodic policy evaluation are essential in ensuring that governance practices remain aligned with Islamic legal and ethical standards. Conclusion: Implementing a Tadrīj-based framework enables BPKH to navigate the dynamic demands of modern financial management without compromising Sharia principles. This approach not only safeguards pilgrims' interests but also strengthens public trust in the institution. Implication: This study contributes to the development of Islamic economic governance by positioning Tadrīj as a practical and scalable model for institutional reform in Sharia-based public fund management. Practically, it offers policy-relevant insights for regulators and Islamic financial institutions seeking to balance legal compliance, financial sustainability, and stakeholder trust in complex economic environments.